Influence of calcium ion deposition on apatite-inducing ability of porous titanium for biomedical applications - Chen, Xiao-Bo; Li, Yun-Cang; Plessis, Johan Du; Hodgson, Peter D.; Wen, Cui’e (Acta biomaterialia, 2009)
In the present study, the influence of calcium ion deposition on the apatite-inducing ability of porous titanium(Ti) was investigated in a modified simulated body fluid (m-SBF). Calcium hydroxide (Ca(OH) 2) solutions with five degrees of saturation were used to hydrothermally deposit Ca ions on porous Ti with a porosity of 80%. Apatite-inducing ability of the Ca-ion-deposited porous Ti was evaluated by soaking them in m-SBF for up to 14 days. Scanning electron microscopy (SEM) and X-ray diffractometry (XRD) confirmed that a thin layer of calcium titanate (CaTiO 3)/calcium oxide (CaO) mixture with a nanostructured porous network was produced on porous Ti substrates after hydrothermal treatment at 200 °C for 8 h. X-ray photoelectron spectroscopy results demonstrated that the content of the Ca ions deposited on Ti and the thickness of the CaTiO 3/CaO layer increased with increasing saturation degree of the Ca(OH) 2 solution. The thickest (over 10 nm) CaTiO 3/CaO layer with the highest Ca content was achieved on the Ti treated in an oversaturated Ca(OH) 2 solution (0.2 M). SEM, XRD, transmission electron microscopy and Fourier transformed infrared spectroscopy analysis indicated that the porous Ti samples deposited with the highest content of Ca ions exhibited the best apatite-inducing ability, producing a dense and complete carbonated apatite coating after a 14 day soaking in m-SBF. The present study illustrated the validity of using Ca ion deposition as a pre-treatment to endow desirable apatite-inducing ability of porous Ti for bone tissue engineering applications.